2020
DOI: 10.1161/jaha.120.016387
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Deficiency and Amiloride Mitigate Angiotensin II–Induced Hypertension in Type 1 Diabetic Mice Suggesting Effects Through the Epithelial Sodium Channel

Abstract: Background Diabetic nephropathy is a common diabetes mellitus complication associated with hypertension, proteinuria, and excretion of urinary plasmin that activates the epithelial sodium channel, ENaC, in vitro . Here we hypothesized that the deletion of plasminogen and amiloride treatment protect against hypertension in diabetes mellitus. Methods and Results Male plasminogen knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…We have previously shown that ECMR‐KO mice do not have elevated blood pressure at baseline or following AngII infusion compared to WT 25 . Furthermore, STZ‐diabetic control mice on a FVB background have no change in blood pressure compared to healthy controls in the 5th week of diabetes by 24h invasive measurements in freely moving unstressed mice 42 . As a result of the uncompensated diabetes with hyperglycemia, glucosuria and 4‐6 times increased diuresis on the FVB background, 42 mice are likely to exhibit extracellular volume contraction which would fit with reactive stimulation of aldosterone secretion and the observed elevated level in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that ECMR‐KO mice do not have elevated blood pressure at baseline or following AngII infusion compared to WT 25 . Furthermore, STZ‐diabetic control mice on a FVB background have no change in blood pressure compared to healthy controls in the 5th week of diabetes by 24h invasive measurements in freely moving unstressed mice 42 . As a result of the uncompensated diabetes with hyperglycemia, glucosuria and 4‐6 times increased diuresis on the FVB background, 42 mice are likely to exhibit extracellular volume contraction which would fit with reactive stimulation of aldosterone secretion and the observed elevated level in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, STZ-diabetic control mice on a FVB background have no change in blood pressure compared to healthy controls in the 5th week of diabetes by 24h invasive measurements in freely moving unstressed mice. 42 As a result of the uncompensated diabetes with hyperglycemia, glucosuria and 4-6 times increased diuresis on the FVB background, 42 mice are likely to exhibit extracellular volume contraction which would fit with reactive stimulation of aldosterone secretion and the observed elevated level in plasma. It is therefore less likely that blood pressure is increased in the present ECMR-KO mice as also observed previously in mouse STZ-diabetes models.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that increased ENaC activity contributes to the development of HS or angiotensin II-induced hypertension [45][46][47][48]. Recently, Andersen et al found that plasminogen deficiency protects against angiotensin II-induced hypertension in type 1 diabetic mice, and this effect was likely mediated by ENaC [21]. Previous studies have demonstrated that the expression of ENaC subunit was increased in hyperglycemic animals [25,26,49]; however, most of these results were observed in rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Randomly selected 8-10 weeks old male WT and Ks-Kir4.1 KO mice received five consecutive days of streptozotocin (Sigma-Aldrich, St Louis, Missouri, USA) injection (i.p.) at 55 mg/kg per day under fasting conditions, whereas mice with the same age and genetic background receiving vehicle (sodium citrate, pH 4.5) were used as controls, as described previously [21]. Two weeks after STZ injection, mice were prepared for experiments by monitoring fasting blood glucose (FBG > 16.7 mmol/l), measured using a glucometer (OneTouch).…”
Section: Induction Of Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Plasminogen (PLG) is correlated with diabetes along with hypertension. 29 Meanwhile, angiotensin I converting enzyme (ACE)…”
Section: Phase I Reactionsmentioning
confidence: 99%